Species and Phylogenetic Diversity of Woody Plants Shift With the Elevational Gradient in Subtropical Forests in South China - Jing Li; Yinghua Luo; Feng Chen; Cong Hu; Chaohao Xu; Zhonghua Zhang; Gang Hu (Ecology and Evolution, 2025)
ABSTRACT The distribution of biodiversity along elevational gradients and the drivers of these patterns are research hotspots in community ecology; nonetheless, these aspects remain insufficiently understood. To address this, we established 24 plots along an elevational gradient from 300 to 1400 m on Daming Mountain, Guangxi, China, and examined the patterns and drivers of species and phylogenetic diversity along this gradient via polynomial regression, generalized linear mixed model, correlation analysis, and redundancy analyses. With increasing elevation, species and phylogenetic diversity showed a hump‐shaped trend, and the phylogenetic structures exhibited clustering at both low and high elevations, whereas at mid‐elevations, a coexistence of clustered and overdispersed structures was observed. Elevation, soil nitrate nitrogen content, and slope collectively constituted the key environmental factors driving the spatial patterns of species diversity. Meanwhile, soil nitrate nitrogen and ammonium nitrogen contents had a decisive influence on phylogenetic diversity. These findings, which reveal the patterns of diversity of woody plant communities along an elevational gradient on Daming Mountain, will contribute to the development of biodiversity conservation strategies for the region.